Acute cholecystitis and residual choledocholithiasis in a situs inversus patient, successful laparoscopic approach and ERCP a case report from Ecuador. (June 2020) - Moyon C, Miguel A.; Rojas, Christian L.; Moyon C, Fernando X.; Aguayo, William G.; Molina, Gabriel A.; Ochoa, Carlos; Neira, Andres; Vinueza, Maria Elena
Abstract: Background: Situs inversus totalis is a rare genetic condition characterized by the transposition of organs to the opposite side of the body, consequently, clinical syndromes show an atypical clinical picture creating a challenge for the surgery team and predisposing to delays in treatment and diagnosis. Laparoscopic cholecystectomy is the gold standard for acute cholecystitis, and in patients with situs inversus, the laparoscopic technique must be modified to accommodate the patient's anatomy. Case presentation: We present the case of a 55-year-old male patient without any past medical history, he presented to the emergency room with abdominal pain in his upper left quadrant. After a thorough examination, acute cholecystitis and situs inversus was diagnosed. He underwent a modified laparoscopic cholecystectomy without complications. In his postoperative period, residual choledocholithiasis was identified and ERCP was done. On follow-ups, the patient is doing well. Conclusions: Although rare and technically demanding, laparoscopic cholecystectomy and ERCP in a patient with situs inversus is feasible. The altered anatomy could lead to complex procedures, therefore proper planning and careful execution of intraoperative techniques are required to treat these patients safely and effectively. Highlights: Situs inversus totalis is a rare condition characterized by the transposition of organs to the opposite side of the body. Laparoscopic cholecystectomy is the gold standard for acute cholecystitis, even in patients situs inversus. Proper planning and careful execution of intraoperative techniques are required to treat these patients safely.